Political economy analysis: Topic Guide - Mcloughlin, Claire (GSDRC, University of Birmingham, 2014)
Political economy analysis (PEA) aims to situate development intervent ions within an understanding of the prevailing political and economic processes in society – specifically, the incentives, relationships, an d distribution and contestation of power between different groups and individuals. Such an analysis can support more politically feasible an d therefore more effective development strategies by setting realistic expectations …